One hundred and fifty years of keeprecords from Pantanos de Villa birds´ - Pulido, Víctor (2018)
The Pantanos de Villa Wildlife Refuge is incorporated into the National System of Protected Areas by the State of Peru. It is located in the south of the city of Lima, between kilometers 18 and 21 of the old South Panamerican Highway in the district of Chorrillos. It has an extension of 263.27 hectares. From De Bernacasse in 1903, he was the first of the naturalist explorers to carry out an inventory of Villa birds, recording 138 species, but it is from 1994 to date, when numerous authors have contributed important information about the birds of this wetland. In the present work, a review and analysis of the research that has recorded 211 species of birds for a hundred and fifteen years, 97 of which are residents and 114 from other latitudes, between migrants, occasional visitors and an introduced species.